Redirection of the Glycolytic Flux Enhances Isoprenoid Production in Saccharomyces cerevisiae. Issue 2 (17th September 2019) - Kwak, Suryang; Yun, Eun Ju; Lane, Stephan; Oh, Eun Joong; Kim, Kyoung Heon; Jin, Yong‐Su
Abstract: Sufficient supply of reduced nicotinamide adenine dinucleotide phosphate (NADPH) is a prerequisite of the overproduction of isoprenoids and related bioproducts in Saccharomyces cerevisiae . Although S. cerevisiae highly depends on the oxidative pentose phosphate (PP) pathway to produce NADPH, its metabolic flux toward the oxidative PP pathway is limited due to the rigid glycolysis flux. To maximize NADPH supply for the isoprenoid production in yeast, upper glycolytic metabolic fluxes are reduced by introducing mutations into phosphofructokinase (PFK) along with overexpression of ZWF1 encoding glucose‐6‐phosphate (G6P) dehydrogenase. The PFK mutations (Pfk1 S724D and Pfk2 S718D) result in less glycerol production and more accumulation of G6P, which is a gateway metabolite toward the oxidative PP pathway. When combined with the PFK mutations, overexpression of ZWF1 caused substantial increases of [NADPH]/[NADP + ] ratios whereas the effect of ZWF1 overexpression alone in the wild‐type strain is not noticeable. Also, the introduction of ZWF1 overexpression and the PFK mutations into engineered yeast overexpressing acetyl‐CoA C‐acetyltransferase ( ERG10 ), truncated HMG‐CoA reductase isozyme 1 ( tHMG1 ), and amorphadiene synthase ( ADS ) leads to a titer of 497 mg L –1 of amorphadiene (3.7‐fold over the parental strain). These results suggest that perturbation of upper glycolytic fluxes, in addition to ZWF1 overexpression, is necessary for efficient NADPH supply through the oxidative PP pathway and enhanced production of isoprenoids by engineered S. cerevisiae . Abstract : Reduced nicotinamide adenine dinucleotide phosphate (NADPH) generation through the oxidative pentose phosphate pathway (oxPPP) is limited in Saccharomyces cerevisiae due to the rigid glycolysis flux. The limitation is bypassed by impeding allosteric upregulation of phosphofructokinase. Along with overexpression of the oxPPP, the phosphofructokinase mutations synergistically enhance the NADPH availability and the NADPH‐dependent isoprenoid biosynthesis in S. cerevisiae without growth defects.